The Views of Literary Critics and Poets about Najib al-Kaylani - Anjum, Salma (Journal of Islamic and Religious Studies, 2016)
Dr. Najib Al- Kailani (1931-1995) is one of the prominent poet and writer of Arabic literature. The multidimensionality of his personality is rare example of the history of Islamic literature. He was a renowned poet, writer, a medical professional, a thinker and overall a great human being. He laid the foundation of the Islamic literature and introduced a sound methodology. His precious literary works in Arabic and Islamic school of thought made his personality more prominent. He not only discusses the issues and challenges faced by Egyptian Muslims but also covers the whole Islamic world and as well as those Muslims who are in minority in their countries. His literary works are a good source of knowledge for not only the general readers but for the intellectuals and writers as well. Research works are being carried out on different dimensions of his personality in different ways by the different universities in the world. Research articles and discussions are being carried out and conferences are also organized in different Arab countries in the memory of Dr Najib Al-Kailani. Kailani was paid rich tributes by Arab writers and thinkers for his unique wealth of literary works. In this article we present the views of Arabian writers about his literary status.